Personal cross-examination of the complainant by the defendant in rape trials : a critical and comparative analysis - O'Sullivan, Sarah Bryan (Trinity College (Dublin, Ireland). School of Law, 2016)
This thesis seeks to address an issue which, until relatively recently, has been neglected in this jurisdiction. The central aim of this research is to consider the issue of personal crossexamination of the complainant by the defendant in rape and sexual offence trials and the potential for prohibiting such cross-examination in this Jurisdiction. In Ireland, a defendant in a rape or sexual offence trial may waive his right to legal representation in favour of selfrepresentation and in doing so, may personally cross-examine a complainant. While other aspects of the rape trial have received significant attention and consequently have been the subject of extensive discussion, debate and reform, this issue is one which remains in need of further consideration in this jurisdiction. This is surprising, particularly due to the fact that the practice of personal cross-examination in rape cases has already been prohibited in many other common law jurisdictions, including England and Wales, New South Wales, New Zealand and Canada ...
Keywords: Law, Ph.D.; PhD Trinity College Dublin, 2016